Temperature and composition effects on elastic properties of CdZnSb solid solution single crystals - Balazyuk, V.N.; Eremenko, A.I.; Raransky, N.D. (Functional Materials, 2008)
Temperature dependences of elastic constant tensor components for Cd₁₋ₓZnₓSb solid solutions have been studies in the 80-300 K range using the pulsed ultrasonic method. It has been found that the Zn content increase in the solid solutions results in enhanced elastic stability of the crystal lattice and reduced anisotropy in mechanical properties of the solid solutions.